Judah Halevi$1 (Bs Fideistic Scepticism in the Kuzaris - Krinis, Ehud (Berlin/Boston De Gruyter, 2020)
The book provides the first comprehensive study on Judah Halevi$1 (Bs use of sceptical tactics in his wrestling with the dogmatic-rationalistic trends of the Arabic culture of his period (11th- 12th centuries).s
Deutsche Forschungsgemeinschaft
English
Hebrew
Keywords: Philosophy; Judaism; Judaism: theology; Jewish studies; Scepticism, Fideism, Arabic; Judeo-Arabic.